Acupuncture Attenuates Inflammation in Microglia of Vascular Dementia Rats by Inhibiting miR-93-Mediated TLR4/MyD88/NF-κB Signaling Pathway. (12th August 2020) - Wang, Lu; Yang, Jing-Wen; Lin, Li-Ting; Huang, Jin; Wang, Xue-Rui; Su, Xin-Tong; Cao, Yan; Fisher, Marc; Liu, Cun-Zhi
Abstract : Background . It is widely accepted that inflammation may contribute to cognitive impairment in patients with vascular dementia (VD). Our prior clinical researches have reported that acupuncture can alleviate cognitive function in VD, but the underlying mechanisms are still unclear. The purpose of this research was to explore whether acupuncture alleviates cognitive impairment by suppressing the microRNA-93- (miR-93-) mediated Toll-like receptor (TLR) signaling pathway, which triggers inflammatory responses in the central nervous system. Methods . VD was established by permanent bilateral common carotid artery occlusion in male Wistar rats. Three days after operation, the rats began daily treatment with acupuncture for two weeks. The levels of miR-93, Toll-like receptors (TLR2 and TLR4), intracellular signaling molecules (myeloid differentiation factor 88 (MyD88) and nuclear factor-kappa B (NF- κ B)), and inflammatory cytokines were subsequently detected. TLR4 colocalized with neurons, microglia, and astrocytes in the hippocampus was evaluated. Neuroinflammation and cognitive function were determined after intracerebroventricular injection of TLR4 antagonist TAK-242 or agonist lipopolysaccharide (LPS) with or without acupuncture. Results . We found that acupuncture notably repressed the expression of inflammatory cytokines in the hippocampus and plasma of VD rats. The expression of TLR4, but not TLR2, was markedly downregulated by acupuncture, accompanied by a decrease in miR-93 and MyD88/NF- κ B signaling pathway activation. The overexpression of TLR4 in microglia, but not in astrocytes and neurons, was reversed by acupuncture. Furthermore, intracerebroventricular injection of TAK-242 had similar effects to acupuncture on inflammation and cognitive function, while LPS injection abolished the beneficial effects of acupuncture. Conclusions . Taken together, these findings provide evidence that acupuncture attenuates cognitive impairment associated with inflammation through inhibition of the miR-93-mediated TLR4/MyD88/NF- κ B signaling pathway in experimental VD. Acupuncture serves as a promising alternative therapy and may be an underlying TLR4 inhibitor for the treatment of VD.